라너와 몰트만의 ‘성례전적 교회’에 나타나는 “세상을 향하는 교회”와 기독교교육 패러다임 - 양금희(YANG Kum-Hee) (Changsin nondan, 2016)
본 연구는 라너와 몰트만의 성례전적 교회 개념과 세상을 향하는 교회의 기독교교육 패러다임에 관한 논문이다. 라너와 몰트만의 성례전적 교회 개념으로부터 이 연구는 ‘성례전적 교회’는 스스로를 위한 기관이 아니라 ‘세상을 위해 존재하는 기관’이라는 것을 발견하였다. 성례전적 교회의 본질은 다음과 같다: 첫째, 성례전적 교회는 세상 속으로 가서 그리스도께서 시작하신 하나님 나라를 구현하는 교회이어야 한다. 둘째, 성례전적 교회는 교회의 존재 자체가 삶으로 표현된성례전이어야 한다. 셋째, 성례전적 교회는 교회의 모든 구성원이 성례전적 존재이어야 한다. 넷째, 성례전적 교회는 세상 속에서의 성례전적 존재로의 소명과 능력이 부여되는 자리여야 한다. 다섯째, 성례전적 교회의 존재양식은 ‘회상과 희망’ 으로, 그리스도의 삶과 고난과 죽음을 현재화하는 회상의 삶을, 또한 종말론적 하나님 나라의 새 창조를 희망하는 삶을 살아야 한다. 성례전적 교회의 본질을 바탕으로 해서 본고는 성례전적 교회의 패러다임을제안하였다: 성례전적 교회는 그 자체로 교육적 존재가 되어야 한다. 전통적 교회는 교사나 사역자가 교육의 주체가 되었다면, 성례전적 교회에서는 ‘교회 자체’ 가 곧 교육의 주체가 되어야 한다. 성례전적 교회에서는 어린이와 청소년만이 아니라 모든 교인이 교육의 대상이어야 하며, 더 나아가 세상 자체가 교육의 대상이되어야 한다. 성례전적 교회는 가르침의 행위가 아닌 존재 자체로서 보여주는 성례전적 교육의 형태를 띠어야 하며 ‘회상과 희망의 원리’가 교육의 원리가 되어야한다. 이상의 것을 살펴보았을 때 성례전적 교회는 오늘날과 같이 사회적 신뢰를상실한 한국교회와 기독교교육이 눈여겨보고 새롭게 추구해야 할 교회와 교회교육의 패러다임이라 하겠다. This study is on the concept of ‘sacramental church’ and educational paradigm of “church toward the world”. It found from the study about concept of sacramental church by Rahner and Moltmann that the sacrmental church is identified not as ‘being for the self’ but as ‘being for the world’, and its nature are following: firstly it is the church goes into the world. Secondly sacramental church is sacramental being itself. Thirdly, whole members of the church must be sacramental being in the world. Fourthly, the sacramental church must be a place where God’s people are empowered for being sacramental in the world. Lastly the lifestyle of the sacramental church must be ‘memory and hope’. It means that the church actualizes the Jesus’ life, passion, and death and lives of hope which realize the new creation of eschatological Kingdom of God here and now. From the study above it suggested the educational paradigm of the church toward the world: sacramental church itself is a educational being and the subject of education. Not only the children and adolescence but the whole church members and also even the world itself are the object of education. Also in terms of the form and method of education, it requires sacramental form in which life and being of the church teaches and especially in forms of ‘memory and hope’. In this sense, the sacramental church is a paradigm which Korean church and Christian education should pay attention to. KCI Citation Count: 2